MXenes for Plasmonic Photodetection - Velusamy, Dhinesh Babu; El‐Demellawi, Jehad K.; El‐Zohry, Ahmed M.; Giugni, Andrea; Lopatin, Sergei; Hedhili, Mohamed N.; Mansour, Ahmed E.; Fabrizio, Enzo Di; Mohammed, Omar F.; Alshareef, Husam N. (Advanced materials (Weinheim), 2019)
MXenes have recently shown impressive optical and plasmonic properties associated with their ultrathin‐atomic‐layer structure. However, their potential use in photonic and plasmonic devices has been only marginally explored. Photodetectors made of five different MXenes are fabricated, among which molybdenum carbide MXene (Mo2CTx) exhibits the best performance. Mo2CTx MXene thin films deposited on paper substrates exhibit broad photoresponse in the range of 400–800 nm with high responsivity (up to 9 A W−1), detectivity (≈5 × 1011 Jones), and reliable photoswitching characteristics at a wavelength of 660 nm. Spatially resolved electron energy‐loss spectroscopy and ultrafast femtosecond transient absorption spectroscopy of the MXene nanosheets reveal that the photoresponse of Mo2CTx is strongly dependent on its surface plasmon‐assisted hot carriers. Additionally, Mo2CTx thin‐film devices are shown to be relatively stable under ambient conditions, continuous illumination and mechanical stresses, illustrating their durable photodetection operation in the visible spectral range. Micro‐Raman spectroscopy conducted on bare Mo2CTx film and on gold electrodes allowing for surface‐enhanced Raman scattering demonstrates surface chemistry and a specific low‐frequency band that is related to the vibrational modes of the single nanosheets. The specific ability to detect and excite individual surface plasmon modes provides a viable platform for various MXene‐based optoelectronic applications. Plasmonic photodetection in Mo2CTx MXene flexible thin films is demonstrated. The photocurrent generation in Mo2CTx is principally controlled by surface plasmon‐assisted hot electrons. The distribution of various surface plasmon modes over individual Mo2CTx nanosheets is visualized by the combination of scanning transmission electron microscopy and ultrahigh‐resolution electron energy‐loss spectroscopy.